Structural imbalance of medical resources amid population mobility and digital empowerment: a study of national and port-developed provinces in China - Haiwei Fu; Junjie Lu (Frontiers in Public Health)
Currently, many cities in China are facing the problem of difficult medical care and expensive medical care, while at the same time a large number of hospitals are on the verge of closing. However, existing literature is unable to adequately explain these phenomena. To fill this gap, this study focuses on the causes of the structural imbalance of medical resources in China from the perspective of population mobility and the governance pathways of digital empowerment. By analyzing the entire country and the port-developed provinces with advanced medical conditions, several key findings are revealed: (1) Different types of medical resources in cities exert differentiated attraction effects on population mobility. High-tier hospitals exert a strong pull on population mobility, while the impact of primary care facilities is not evident; (2) Continuous population movements lead to a structural imbalance of medical resource, characterized by overburdened high-tier hospitals coexisting with underutilized primary care facilities; (3) Economic development has increased people’s emphasis on health and prevention of critical illnesses, making the aforementioned structural imbalance more pronounced in the port-developed provinces of China; (4) Digital empowerment offers a new perspective for addressing these issues. By introducing digital diagnostic devices in primary care facilities, the likelihood of major diseases can be swiftly assessed. This technology not only enables intelligent triage but also effectively mitigates the structural imbalance of medical resources.